Who was James? Essays on the Letters Authorship and Provenance - Becker, Eve-Marie; Luther, Susanne; Jónsson, Sigurvin Lárus (Mohr Siebeck, 2022)
Wer war Jakobus? Essays zur Autorschaft und Herkunft des Briefes.
PublicationDate: 20220730
Keywords: Early Christian Literature -- Epistolography -- Antioch -- Letter of James -- epistolary authorship -- Cultural heritage -- early Christian literature -- epistolography -- Neues Testament -- Array